ON THE GENESIS OF THE WORD NASTOLOVANI IN CZECH SLAVONIC AND OLD CZECH - Karlikova, Helena (Bohemica Olomucensia, 2020)
The word nastolovani denotes enthroning, raising somebody to the throne. Since the Middle Ages the term ``enthroning'' is in many European languages basically the only official meaning used for this ceremony. In his dictionary F. Miklosich records the verb nastolovati with the meaning 'in throno collocare' and the adjective nastolovanъ 'in throno sedens'. It is obviously a derivative of the Old Church Slavonic noun stolъ, which was, in Old Church Slavonic translation texts, a usual equivalent of Greek θρόνς 'armchair, seat; (in the New Testament) royal seat, throne'. Old Czech lacks a verb equivalent to the mentioned Czech Slavonic verb (attested is only perfective nastoliti), though it has the deverbal noun nastolovanie 'raising to the throne'. This noun occurs only in a name of one of religious feasts which is used to be called Nastolovanie svateho Petra [Raising Saint Peter to the throne] in Old Czech documents. The contribution tries to find out whether Church Slavonic nastolovati could be regarded as a calque from Greek and whether Old Czech nastolovanie could be viewed as a Church Slavism.
Keywords: Old Church Slavonic; Old Czech; calque; Church Slavism; etymology